THE ROUTE OF THE HOLY GRAIL: FROM SAN JUAN DE LA PEÑA TO VALENCIA. THE STRUCTURING OF A TERRITORY BASED ON ORAL TRADITION - García, Ana Mafé (Journal of Tourism, Sustainability and Well-being, 2018)
The Route of the Holy Grail was presented FITUR 2017 (Madrid, January 2017) by the Agència Valenciana del Turisme. It involves structuring a routethat connects the communities of Aragon and Valencia by use of touristic description that encompasses history, art, rituals and oral traditions and which is based on the knowledge of what was known in the Middle Ages as the “search for the Grail”. In this article we wish to show the importance of the oral tradition that has been received and perpetuated through an object of fundamental importance: the Holy Chalice, safeguarded in the Cathedral of Valencia. In addition to presenting its history and verifying it as a tangible patrimonial asset, the Holy Chalice is underpinned by intangible oral traditions that allow us to establish a route, a new path of knowledge from San Juan de la Peña to Valencia. The methodology of our work is centered on reviewing the available documented sources about the Route of the Holy Grail and contrasting them with those agents who have intervened in them - their contributions and promotion of this heritage - with the aim of clearly identifying the principal force behind the generation of this historic, artistic and religious route. At the same time, we are contributing to cultural tourism from the perspective of art history by constructing a touristic description based on the knowledge and study of the local heritage. We also present the work carried out by the Association of the Camino del Santo Grial to structure this overland route from San Juan de la Pena to the Cathedral of Valencia. In the Conclusion section, we close our research article with an explanation of how Valencia, Territorio Grial can offer a new type of tourism full of intangible richness for the intrepid visitor who wishes to learn about and experience the search for the Grail.